Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1989
DOI: 10.1115/89-gt-87
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Partial Length Circular Pin Fins as Heat Transfer Augmentors for Airfoil Internal Cooling Passages

Abstract: Pin fins are commonly used as heat transfer augmentors for internal cooling of turbine airfoils. These pins may extend from one wall to the other or may be segmented to meet specific requirements of removing the airfoil’s varying heat load. Three configurations of the partial pins were tested in a 25:1 aspect ratio channel and the results are compared with those for the full pins. The array average heat transfer rate decreases linearly with increasing gap and is bounded by the value for full pins at one end an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Their results showed that the partial length pin fins did not outperform the full length fins in terms of heat transfer but when the heat transfer and pressure loss are both considered, some of their partial length pin fin arrays were superior. Arora and Abdel-Messeh [2] also investigated the partial length circular pin fin concept and found that both the array averaged heat transfer and friction factor decreases with increasing gap distance. Pin fins with oblong cross-sections are investigated by Metzger et al [3] for various pin orientations with respect to the main flow.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the partial length pin fins did not outperform the full length fins in terms of heat transfer but when the heat transfer and pressure loss are both considered, some of their partial length pin fin arrays were superior. Arora and Abdel-Messeh [2] also investigated the partial length circular pin fin concept and found that both the array averaged heat transfer and friction factor decreases with increasing gap distance. Pin fins with oblong cross-sections are investigated by Metzger et al [3] for various pin orientations with respect to the main flow.…”
Section: Introductionmentioning
confidence: 99%
“…Chyu et al used cube and diamond shaped pins to enhance the heat transfer coefficient from a surface [22]. The cubeshaped pins have the highest mass transfer coefficients among the shapes considered and round pins have the lowest mass transfer coefficients.…”
Section: Pin-fin Coolingmentioning
confidence: 99%
“…Arora and Abdel -Messeh studied the effects of partial length pins in a rectangular channel [10]. The surface containing pins is not affected by the pin tip clearance.…”
Section: Pin Array and Partial Length Pin Arrangementmentioning
confidence: 99%